Validation of a novel instrumentation (FlexOmega system) measuring oar bending moments on-water in rowing - Ungricht, C.; Graf, C.; Mandanis, G.; Wernas, T.; Schmid, M. J.; Wolf, P. (Current Issues in Sport Science, 2023)
Quantifying rowing performance can facilitate control of training load or assessment of skill level. Accordingly, the FlexOmega system was developed, which records the bending moment of the oar. This work aimed to validate this new instrumentation during a dynamic load case. Two force profiles were first derived from bending moments acquired during on-water rowing (one at race pace, one at training pace). These force profiles were then used to repeatedly load the instrumented oar on a newly developed test bench. To ultimately elaborate how precision and accuracy determined on the test bench affects everyday training, i.e., whether practitioners can reasonably use the FlexOmega system, the measurement variability observed on the test bench was related to the measurement variability seen for on-water mea surements.